2014
DOI: 10.1093/qjmed/hcu025
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy for type 1 diabetes

Abstract: Cell therapy in the form of human islet transplantation has been a successful form of treatment for patients with type 1 diabetes for over 10 years, but is significantly limited by lack of suitable donor material. A replenishable supply of insulin-producing cells has the potential to address this problem; however to date success has been limited to a few preclinical studies. Two of the most promising strategies include differentiation of embryonic stem cells and induced pluripotent stem cells towards insulin-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
0
17
0
4
Order By: Relevance
“…Clinical islet transplantation has been shown to be a viable option for treatment of type 1 diabetes . Xenotransplantation of porcine islets is a promising alternative to bridge the gap between available human cells and the needs of patients with diabetes .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical islet transplantation has been shown to be a viable option for treatment of type 1 diabetes . Xenotransplantation of porcine islets is a promising alternative to bridge the gap between available human cells and the needs of patients with diabetes .…”
Section: Introductionmentioning
confidence: 99%
“…A small number of pluripotent cell lines have been used to form islets for transplantation, in which these cells would be generated, maintained, and differentiated under GMP-grade condition and expected to expand up to 1 million islets for a single transplantation [12].…”
Section: Differentiation Of Pluripotent Stem Cells Into β-Cellsmentioning
confidence: 99%
“…Currently, it is still not possible to turn stem cells further into 100% functional β-cells, however, in a study involving streptozotocin (STZ)-induced diabetic mice, the cells that were implanted under kidney capsule or epididymal fat pad, were capable of secreting C-peptide as a response to glucose after 12 weeks. It is important to note that C-peptide at the normal range indicates good response to tolerance test, which means that even a small amount of insulin production is beneficial for glycemic control [12].…”
Section: Differentiation Of Pluripotent Stem Cells Into β-Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that mouse ESCs can differentiate into neural stem cells, pancreatic β cells, hematopoietic stem cells, cardiomyocytes, and osteoblasts after induction in vitro. ESCs can be used for tissue repair and functional replacement therapy, which may provide a new strategy for future treatment of some irreversible diseases such as heart failure, hereditary diseases, diabetes, and neuronal degeneration [1][2][3].…”
Section: Introductionmentioning
confidence: 99%